Tax risk, environmental uncertainty, and tax avoidance: Does financial distress matter? - Januardi Januardi; Estralita Trisnawati; Amrie Firmansyah (Universitas Pamulang, 2022)
This study examines the effect of tax risk and environmental uncertainty on tax avoidance. In addition, this study also employs financial distress as a moderator of the relationship between tax risk and environmental uncertainty on tax avoidance. This study employs manufacturing company data from the Indonesia Stock Exchange from 2016 to 2021 with a total sample of 65 companies. The total number of observation data in this study is 390. Panel data regression test using the random effect model is employed to test the hypothesis in this study. The results of this study indicate that tax risk cannot influence tax avoidance, while environmental uncertainty has a positive effect on tax avoidance. Furthermore, financial distress cannot strengthen the positive effect of tax risk on tax avoidance, while financial distress can strengthen the positive effect of environmental uncertainty on tax avoidance.AbstrakPenelitian ini bertujuan untuk menguji pengaruh risiko pajak dan ketidakpastian lingkungan terhadap tax avoidance. Penelitian ini juga menggunakan kesulitan keuangan sebagai pemoderasi hubungan antara risiko pajak dan ketidakpastian lingkungan terhadap tax avoidance. Penelitian ini menggunakan data perusahaan manufaktur yang didapatkan dari Bursa Efek Indonesia dari tahun 2016 sampai dengan tahun 2021 dengan jumlah sampel sebanyak 65 perusahaan sehingga jumlah data observasi dalam penelitian ini sebanyak 390 data. Uji regresi data panel dengan menggunakan random effect model digunakan untuk menguji hipotesis pada penelitian ini. Hasil penelitian ini menunjukkan bahwa risiko pajak tidak dapat memengaruhi tax avoidance, ketidakpastian lingkungan berpengaruh positif terhadap tax avoidance. Selanjutnya, kesulitan keuangan tidak dapat memperkuat pengaruh positif risiko pajak terhadap tax avoidance, sedangkan kesulitan keuangan terbukti dapat memperkuat pengaruh positif ketidakpastian lingkungan terhadap tax avoidance.